Nature Speaks, Poetry Responds - Vieira, Mauricio (Revista Cerrados, 2022)
The article explores the ancient link between plants and poetry, evoking poetry’s early connection with healing rituals and its expression throughout history until the present day, when the climate crisis makes imperative a closer proximity to nature by virtue of the feelings and sensations that poetry can invoke in regard to nature’s beauty and power of creation